Survival Weighted Pareto Distribution: Order Statistics and Its Applications (European Journal of Pure and Applied Mathematics, 2025)
Nagy et al. [1]  proposed an extended Pareto distribution called a survival-weighted Pareto distribution (SWPD). The proposed model proves to be the best fit for several extensions of the Pareto distribution. The current study provides quantitative features of SWPD through order statistics. The SWPD is characterized through the hazard rate function (HRF). The appropriateness of the characterization result is verified empirically by using a real-life data set. Finally, the measures of inequality are taken into consideration due to the heavy tail properties of the model.
Keywords: SWPD, Order statistics, Moments, Characterization, Inequality measures.